Fundamental Significance of Physical Activity for Seniors' Health - Katarzyna Sygit (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2015)
Physical activity is a basic component of geriatric prevention. Lower physical activity of seniors is a cause and effect of many chronic conditions, e.g. type 2 diabetes, obesity, diseases of musculoskeletal system or cancer. This paper analyzes Polish and international literature in terms of significance of physical activity for keeping and improving health of seniors. Numerous studies carried out at large research facilities all over the world proved that taking up physical activity by seniors is one of the key factors for ensuring better health. It is, however, important to precede workout with medical examination. After that, suitable exercises, their frequency, duration and intensity need to be determined. The conclusion of this paper is as follows: regular physical activity improves effectiveness of preventive measures and treatments related to diseases such as cardiovascular disease; it also reduces mortality rate and prolongs the period of physical and mental activity of seniors.